Formation of European Integration Development Strategy of Ukraine - Podorozhnii, Ye. Yu.; Подорожній, Є. Ю.; Boldizhar, Sandra; Sofilkanich, O.; Подорожній Євген Юрійович (Baltic Journal of Economic Studies. – 2018. - Vol 4, № 1. – Р. 283–292, 2018)
Сьогодні євроінтеграція - це стратегічний курс України, швидкість якого збільшується. Це зобов'язує звернути увагу на наслідки європейської інтеграції. Європейська інтеграція, тобто формування і подальше зміцнення зв'язків з європейськими країнами, носить комплексний характер. Актуальність теми статті визначається об'єктивним характером європейського інтеграційного процесу в українській економіці і комплексністю наслідків цього процесу. Метою статті є аналіз впливу процесу європейської інтеграції на економічний розвиток країни на основі сценарного підходу.

Today European integration is a strategic course of Ukraine, its speed increases. It obliges to pay attention to the consequences of European integration. European integration, that is, formation and further strengthening of ties with European countries, has a complex nature (economic, political, social, cultural, etc.) at all levels – transnational, interregional, between separate economic entities. The relevance of the article’s topic is determined by objective nature of European integration process in Ukrainian economy and complex nature of consequences of this process. The purpose of the article is the analysis of the influence of European integration process on the economic development of the country on the basis of scenario approach. The presence of essential regional imbalances in the socio-economic development in Ukraine requires differentiated approaches to the elaboration of development measures aimed at promoting the creation of free trade area, as well as strengthening economic and sectoral cooperation between Ukraine and the EU. Thus, there appears a necessity to monitor and evaluate progress of economic reforms in regions of Ukraine in the context of European integration processes in order to reveal strengths and weaknesses, to substantiate priorities and means of their achievement, as well as possibility of their timely adjustment for improving the region’s ability to follow the vector of European integration. For the purpose implementation, it seems most appropriate to calculate an integral value – European Integration Index (Ір). In the most general terms, the index is a relative magnitude, designed to fulfil the role of a generalized measure of a certain phenomenon, which is formed under the influence of heterogeneous components, which cannot be directly summed up. European integration consequences for the economy of Ukraine are considered and it is shown that these consequences can have not only a positive nature in the form of new opportunities and open markets but also pose a threat. Scenarios for changing the national economy of Ukraine as a result of the influence of European integration processes are determined. A description for each of these scenarios is provided. Assessment of such scenarios is done according to criteria of desirability, probability, and time of realization. A relation between the considered scenarios for changing the national economy of Ukraine over the influence of European integration processes taking into account probabilistic cause-and-effect relationships between individual scenarios is shown. Consequences of these scenarios for the economic development of Ukraine are presented. The research result is the detection and characteristic of scenarios of changes in the economy of Ukraine as a result of the influence of European integration processes, as well as the characteristic of the influence of such scenarios on the country’s economic development. Scientific novelty of research results is defining scenarios of changes in Ukrainian economy under the influence of European integration processes, characteristics of these scenarios and relations among them taking into account the influence of such scenarios on the country’s economic security. The practical value of research results is considered a possibility to provide adaptation of regions of Ukraine to the consequences of European integration processes in the economic and legal field.

Сегодня евроинтеграция - это стратегический курс Украины, скорость которого увеличивается. Это обязывает обратить внимание на последствия европейской интеграции. Европейская интеграция, то есть формирование и дальнейшее укрепление связей с европейскими странами, носит комплексный характер. Актуальность темы статьи определяется объективным характером европейского интеграционного процесса в украинской экономике и комплексностью последствий этого процесса. Целью статьи является анализ влияния процесса европейской интеграции на экономическое развитие страны на основе сценарного подхода.
Keywords: Міжнародне право .International Law. Международное право; Наукові публікації. Scientific publications. Научные публикации; Європейський Союз; European Union; Европейский Союз; європейська інтеграція; European integration; европейская интеграция; євроінтеграційний процес; eurointegration process; евроинтеграционный процесс; економічне зростання; economic growth; экономический рост; publikatsii u WoS; publikatsii u zarubizhnomu vydanni